2020
DOI: 10.31849/reila.v2i3.4603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vocabulary Learning Strategies on Gender Based ESL Learners in Pakistan

Abstract: The wide spectrum of English language compels readers to find out the exact crux of the language itself. English has won the status of international language. It has become a dire need of this age. The English language is comparatively difficult due to its pronunciation, sentence structure and vocabulary level from local languages in Pakistan. Vocabulary is the utmost aspect of learning a second language. It is the essence and soul of language. The language process depends on learning vocabulary. So the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Besides, the role of gender, grades, learning environment, and age context on vocabulary learning strategies has also been investigated. However, similar to the previous variable, studies on the relationship between vocabulary learning strategies and gender found mixed and inconsistent results, such as in (Bhatti & Mukhtar, 2020) and (Gorgoz & Tican, 2020). The previous studies in the Indonesian context did not connect the VLSs to individual differences such as gender.…”
Section: Introductionsupporting
confidence: 54%
“…Besides, the role of gender, grades, learning environment, and age context on vocabulary learning strategies has also been investigated. However, similar to the previous variable, studies on the relationship between vocabulary learning strategies and gender found mixed and inconsistent results, such as in (Bhatti & Mukhtar, 2020) and (Gorgoz & Tican, 2020). The previous studies in the Indonesian context did not connect the VLSs to individual differences such as gender.…”
Section: Introductionsupporting
confidence: 54%
“…Vocabulary is among the English abilities, play a critical role in both language learning and production. It is even likened to the soul and the heart of the language, and becomes the first step in learning a language (Bhatti & Mukhtar, 2020;Qomariyah & Nafisah, 2020). Individuals who have mastery of vocabulary in foreign languages would find it easier to learn languages because language is all about words.…”
Section: Introductionmentioning
confidence: 99%